Biologics for eosinophilic oesophagitis: a systematic review and meta-analysis - Beibei Zeng; Doudou Jia; Shengen Li; Xuna Liu; Boxu Zhu; Yanqi Zhang; Yan Zhuang; Fei Dai (Annals of Medicine)
Objective Advancing the understanding of the pathophysiology of eosinophilic oesophagitis (EoE) and other eosinophilic gastrointestinal diseases (EGIDs) has spurred research into targeted biological therapies, while the conclusive therapeutic efficacy of biologics remains uncertain. In this review, we conducted a meta-analysis of all RCTS of biologics in the treatment of EoE to evaluate their efficacy and safety and discussed their treatment of non-EoE EGIDs.Methods We searched the PubMed, EMBASE, Cochrane Library, and Web of Science databases. Double-blind randomized controlled trials comparing biologics with placebo in patients with EoE and non-EoE EGIDs were collected and further screened for inclusion and exclusion. The caliber of the included literature was evaluated using the Cochrane risk assessment tool findings. Data extraction and meta-analysis were conducted using RevMan 5.4 and Stata 17.0. Clinical response and histological remission were the major endpoints.Results Our search retrieved 3,237 articles. There were seven trials in total, comprising 792 people with EoE. Key outcomes of this meta-analysis include the following: Anti-IL-5 biologics exhibited statistically significant benefits in histological remission (RR 2.03 [CI 1.45–2.85]; p < 0.0001) compared to the placebo, but there was no significant difference in symptom relief (RR 1.06 [CI 0.88 to 1.28]; p = 0.53); anti-IL-4/13 biologics had significant effects on histologic improvement (RR 10.48 [CI 5.54–19.82]; p < 0.00001) and symptom related score reduction (RR 1.44 [CI 1.08–1.93]; p = 0.01), with a better outcome for endoscopic remission than with placebo (SMD–1.06 [CI–1.26–0.86], p < 0.00001); no statistically significant differences in adverse effects were observed between the intervention and control groups.Conclusions Our findings suggest that the biologics currently being investigated are considered safe and effective treatments for EoE, while their efficiency varies. However, the discussion of biologics in non-pharyngitis EGID is hampered by a lack of research, necessitating more research in high-quality trials.